2020
DOI: 10.1371/journal.pone.0231013
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma-induced protein 10 (IP-10) and cardiovascular disease in African Americans

Abstract: Biomarkers of chronic inflammation (such as C-reactive protein) have long been associated with cardiovascular disease and mortality; however, biomarkers involved in antiviral cytokine induction and adaptive immune system activation remain largely unexamined. We hypothesized the cytokine interferon gamma inducible protein 10 (IP-10) would be associated with clinical and subclinical cardiovascular disease and all-cause mortality in African Americans. We assessed these associations in the Jackson Heart Study (JHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Recently, it was demonstrated that CXCL10 is a circulating inflammatory marker in patients with advanced heart failure (Altara et al, 2016b ). Similarly, it is also reported that circulating levels of CXCL10 is associated with heart failure (Leavitt et al, 2020 ). These clinical findings demonstrate that blood concentration of CXCL10 is elevated in patients with heart failure; however, the mechanisms of CXCL10 induction remain to be addressed.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, it was demonstrated that CXCL10 is a circulating inflammatory marker in patients with advanced heart failure (Altara et al, 2016b ). Similarly, it is also reported that circulating levels of CXCL10 is associated with heart failure (Leavitt et al, 2020 ). These clinical findings demonstrate that blood concentration of CXCL10 is elevated in patients with heart failure; however, the mechanisms of CXCL10 induction remain to be addressed.…”
Section: Discussionmentioning
confidence: 81%
“…IP-10 (also known as C-X-C motif chemokine ligand 10, CXCL10) is a chemokine with pro-inflammatory and anti-angiogenic properties, of which the role in the connection between inflammation and angiogenesis has been previously proposed [ 43 ]. The involvement of IP-10 with atherosclerosis and coronary syndromes has also been suggested [ 44 ], and in recently published cohort data, IP-10 has been shown to have a role in heart failure and its associated mortality in African Americans [ 45 ]. Over the last two decades, different studies, both experimental and clinical, have already tried to understand the role of IP-10 in cardiovascular diseases, but its actions are complex and seem to be associated with the type of receptor it binds to [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines are a group of immune mediators known to mediate cell migration. IP-10 binds to its CXCR3 receptor to induce chemotaxis as well as apoptosis, cell growth and angiostasis [19]. Alterations in IP-10 levels have been associated with in ammatory diseases including infectious diseases, immune dysfunction and tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in IP-10 levels have been associated with in ammatory diseases including infectious diseases, immune dysfunction and tumour development. IP-10 is also suggested to play a role in heart failure and in mortality risk in general [19,20].…”
Section: Discussionmentioning
confidence: 99%